Possibilities of using immersive learning based on abstract highly formalized mathematical models for training future mathematics teachers - Valentina A. Matveeva; Olga Yu. Zaslavskaya (RUDN Journal of Informatization in Education)
Problem statement . Immersive technologies are becoming a hallmark of the modern educational process today by allowing users to immerse themselves in a virtual environment, create a sense of presence and engagement through high interactivity and realism of visual and audio effects. Dynamic models provide a mathematical description of system behavior over time in different domains. In the context of immersive learning based on abstract highly formalized mathematical models for preparing future mathematics teachers, dynamic models provide the basis for creating interactive and realistic virtual environments. Teaching mathematics is usually associated with abstract highly formalized mathematical models. “Observing” an abstract highly formalized mathematical model is a complex dynamic process that is consistent with its behavior in real-world processes, although these processes are not always possible to visualize. The purpose of this work is to describe the technology of ‘weak immersive learning’. Methodology . The study of the problem is considered using the example of the mathematics section “Number Theory”. The asymmetric RSA encryption system is chosen as the observed model. To bring the studied model closer to the real situation, the Maxima computer algebra system is used. Results . In the process of studying the mathematical model of the RSA cryptosystem and its implementation in the Maxima computer algebra system, students experience a ‘partial’ immersion in the environment being studied, since to observe the results it is necessary to know the mathematical model and a number of functions that can provide a certain result. However, the pedagogical process is accompanied by the following principles: immersion in context, interactivity, personalization, motivation, assessment, and accessibility. Conclusion . Thus, the technology under consideration can be called ‘weak immersive learning’, since visual effects and creation of a computer model require the direct participation of the student and theoretical knowledge of the subject.